Analysis of liquidity company size company growth and capital structure on profitability - Maulien Safa Mirella; Titiek Suwarti (Enrichment : Journal of Management, 2023)
The property sector is one of the sectors that plays a major role in the national economy, but property companies have large business risks and lack regulation. This study focuses on analyzing the effect of liquidity, company size, company growth, and capital structure on the profitability of property companies listed on IDX 2017-2021. This research is a type of descriptive quantitative research using secondary data on annual financial statements which are then analyzed using multiple linear regression. Through purposive sampling technique, a research sample of 190 annual financial reports from property companies was selected. The results of the study explained that liquidity and company size did not have a significant effect. Company Growth had positive effect, while capital structure had negative significant effect on the profitability of property companies listed on IDX for the 2017-2021 period.